RESOLUTION OF SEROLOGICAL ABO DISCREPANCY IN A TERTIARY CARE SET-UP OF WESTERN ODISHA - Dr. Deepak Kumar Dasmohapatra; Dr. Anuradha Panda; Dr. Saradbrata Mishra; Dr. Babita Ekka; Dr. Aditya Narayan Dash (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: This study was conducted to identify the patient's precise blood type, prevent the recipient from receiving incompatible blood transfusions, avoid HDFN (Hemolytic Disease of the Fetus and Newborn), and identify rare blood phenotypes such as Bombay and para-Bombay, among others.Methods: This hospital-based prospective study tested blood grouping using 25,559 patient blood samples from the Department of Transfusion Medicine at the Veer Surendra Sai Institute of Medical Science and Research, Burla, Odisha. The study was conducted from October 2016 to May 2018, after obtaining participant written informed consent and institutional ethics committee approval.Results: The common cause of sample-related blood group disagreement was cold autoantibody. The primary causes of variations in red cell testing in our investigation were malignancy and autoagglutinin or excess protein coating red cells. In 1.92% of cases with weak red cell reactivity, malignancy was present. Increased red cell activity in autoagglutinins was primarily responsible for the most prevalent red cell disparities (40.38%). The two primary causes of weak or absent serum reactivity that interfered with serum testing in our investigation were hypogammaglobulinemia and the elderly. In hypogammaglobulinemia and senior patients, the frequency of disagreement was 2.8% and 5.76%, respectively. In our investigation, the infectious patient's serum revealed 3.84% group differences. Five of the 52 cases with inconsistencies were caused by elderly patients. Out of the five old patients, four belonged to group-O and one to group B. The senior patients' ages ranged from 70 to 107 years, with a mean age of 92 years (92.4).Conclusion: It's critical to identify and address inconsistent outcomes. To avoid ABO incompatibility, a person must have their blood type labeled correctly. It is critical to always pay attention to the intensity of the response, because weaker responses typically raise questions.